Enhancing breast cancer treatment: mesoporous dopamine nanoparticles in synergy with chrysin for photothermal therapy - Zhu, Jing; Zhang, Heng; Lan, Haomiao; Bi, Bing; Peng, Xianfeng; Li, Dandan; Wang, Haili; Zhu, Ke; Shao, Fuqiang; Yin, Minggang (Frontiers in Oncology, 2024)
Introduction Breast cancer is one of the most prevalent cancers, primarily affecting women. Among its subtypes, estrogen receptor-positive (ER+) breast cancer is particularly common. Inhibiting estrogen's effects is crucial for treating ER+ breast cancer, but current therapies often have significant side effects and limitations. Chrysin, a natural flavonoid, has shown potential in reducing estrogen receptor expression, but its poor water solubility hampers clinical application. This study explores the use of mesoporous dopamine nanoparticles (mPDA) to enhance the delivery and efficacy of Chrysin, combined with photothermal therapy (PTT), for breast cancer treatment. Methods Chrysin-loaded mPDA nanoparticles (Chrysin@mPDA) were synthesized and characterized for their morphology, drug-loading efficiency, stability, and photothermal properties. Network pharmacology was used to predict Chrysin's mechanisms in breast cancer, which were validated through gene expression analysis in cell experiments. The therapeutic efficacy of Chrysin@mPDA with and without PTT was evaluated in a mouse model of breast cancer, with tumor volume and weight measured. Immunohistochemical analysis was conducted to assess estrogen receptor expression and immune cell infiltration in tumor tissues. Results Chrysin@mPDA nanoparticles demonstrated a high drug-loading capacity and excellent stability. Photothermal studies confirmed the nanoparticles' ability to generate heat upon laser exposure, significantly enhancing Chrysin release in acidic conditions with laser irradiation. Network pharmacology identified key target genes affected by Chrysin, including ESR1, BRCA1, CTNNB1, and BAX, which were validated through qPCR. In vivo, the combination of Chrysin@mPDA and PTT significantly reduced tumor volume and weight, decreased estrogen receptor-positive cells, and increased infiltration of CD3+CD4+ and CD3+CD8+ T cells in tumor tissues. Discussion The study highlights the potential of Chrysin-loaded mPDA nanoparticles combined with PTT as an effective strategy for breast cancer treatment. This approach addresses the limitations of Chrysin's solubility and enhances its therapeutic efficacy through synergistic mechanisms. The dual action of Chrysin in modulating gene expression and PTT in inducing localized hyperthermia and immune response suggests a promising avenue for improved breast cancer prognosis and reduced recurrence.